Biosynthesis of antibacterial silver nanoparticles using plant organs of Ficus deltoidea Jack var. kunstleri (King) corner - Mohammad Din, Shahrulnizahana (2022)
The wide range of silver nanoparticle (AgNP) applications in industrial and biomedical disciplines has elevated their demand. Physical and chemical methods of AgNP synthesis are ecological harmful due to the generation of toxic by-products and high energy consumption. However, this drawback can be solved by using plant extract to synthesize AgNP because it is environmentally friendly and cost-effective. Hence, this study explored and evaluated the ability of extracts from different plant organs (leaf, stem, fig and root) of Ficus deltoidea Jack var. kunstleri (King) Corner (Mas Cotek) on AgNP production. The AgNP was characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), energy dispersive X-ray (EDX), and thermogravimetric-differential thermal analysis (TGA-DTA). The result showed that liquid chromatography mass spectroscopy (LCMS) detected more than 100 phytochemical compounds present in the extracts and approximately 50% of them belong to phenolic and flavonoid compounds. Vitexin and isovitexin were discovered only in leaf, while fig had the highest total phenolic content (TPC) and total flavonoid content (TFC). Approximately, 92% of 107 mg/L Ag+ precursor was successfully collected as AgNP when stem extract was used while 71%, 48% and 39% for AgNP-Root, AgNP-Fig and AgNP-Leaf, respectively. Outcome from the optimization of synthesizing condition, the highest peak of the localized surface plasmon resonance (LSPR) from AgNP-Fig was observed which was 5.7 (a.u.), which aligned with the high TPC and TFC values. The optimal synthesizing conditions for each organ extract in synthesizing AgNP were different; leaf (1.0 mL, 30 hours, 60°C, pH 10), stem (1.0 mL, 21 hours, 90°C, pH 12), fig (0.8 mL, 33 hours, 100°C, pH 10) and root (3.0 mL, 21 hours, 90°C, pH 12). All AgNP was found to be stable for 26 days. It was observed that the AgNP particles were spherical, and the size was in the order of AgNP-Root (15.4 ± 3.4 nm) < AgNP-Stem < AgNP-Fig < AgNP-Leaf. Meanwhile, AgNP-Root and AgNP-Stem showed antibacterial activity when tested using disc diffusion technique (DDT) and minimum inhibitory/bactericidal concentration (MIC/MBC) against Escherichia coli and Staphylococcus aureus bacteria due to its small particle size. In addition, visible damage on the bacterial wall of S. aureus was observed when treated with AgNP-Stem. Finally, human skin fibroblast (HSF 1184) cells exhibited lower viability when treated with AgNP-Root and AgNP-Stem compared to AgNP-Fig and AgNP-Leaf. In conclusion, this research showed the diversity and complexity of phenolic and flavonoid compounds in each plant organs of F. deltoidea were able to synthesize distinct characteristics of AgNP, and subsequently small-sized of AgNP-Root and AgNP-Stem significantly impacted their antibacterial property.